Multidrug Resistance in Enterococci Isolated From Wild Pampas Foxes (Lycalopex gymnocercus) and Geoffroy's Cats (Leopardus geoffroyi) in the Brazilian Pampa Biome - Oliveira de Araujo, Gabriella; Huff, Rosana; Favarini, Marina Ochoa; Mann, Michele Bertoni; Peters, Felipe Bortolotto; Frazzon, Jeverson; Guedes Frazzon, Ana Paula (Frontiers in Veterinary Science, 2020)
Enterococci are ubiquitous microorganisms present in various environments and within the gastrointestinal tracts of humans and other animals. Notably, fecal enterococci are suitable indicators for monitoring antimicrobial resistance dissemination. Resistant bacterial strains recovered from the fecal samples of wild animals can highlight important aspects of environmental disturbances. In this report, we investigated antimicrobial susceptibility as well as resistance and virulence genes in fecal enterococci isolated from wild Pampas foxes (Lycalopex gymnocercus) (n = 5) and Geoffroy’s cats (Leopardus geoffroyi) (n = 4) in the Brazilian Pampa biome. Enterococci were isolated from eight out of nine fecal samples and Enterococcus faecalis was identified in both animals. However, E. faecium and E. durans were only detected in Pampas foxes, while E. hirae was only detected in Geoffroy’s cats. Antimicrobial susceptibility analysis showed frequent resistance to rifampicin (94%), erythromycin (72.6%), ciprofloxacin/norfloxacin (40%), streptomycin (38%), and tetracycline (26%). The high frequency of multidrug-resistant enterococci (66%) isolated in this study is a matter of concern since these are wild animals with no history of therapeutic antibiotic exposure. The tetM/tetL and msrC/ermB genes were detected in most tetracycline- and erythromycin-resistant enterococci, respectively. The gelE, ace, agg, esp, and clyA virulence genes were also detected in enterococci. In conclusion, our data suggest that habitat fragmentation and anthropogenic activities in the Pampa biome may contribute to high frequencies of multidrug-resistant enterococci in the gut communities of wild Pampas foxes and Geoffroy’s cats. To the best of the authors’ knowledge, this is the first report of antimicrobial-resistant enterococci in the Pampa biome.